2016
DOI: 10.1007/s13193-016-0538-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep Vein Thrombosis in Indian Cancer Patients Undergoing Major Thoracic and Abdomino-Pelvic Surgery

Abstract: The aim of the study was to determine the incidence of postoperative deep vein thrombosis (DVT) in Indian patients undergoing surgery for thoracic and abdomino-pelvic malignancies.A prospective observational study was conducted in a tertiary care cancer centre in North India. Two hundred and fifty consecutive patients who underwent curative surgery for thoracic and abdomino-pelvic malignancies during the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Arbeit et al [13] have shown overall 13.6% incidence of DVT after groin dissection with no benefit of pharmacological heparin prophylaxis. Various studies have shown low incidence of DVT in Indian patients [14,15]. Apart from ethnicity, early ambulation and routine use of mechanical prophylaxis might have resulted in zero incidence of DVT/PE in the present series.…”
Section: Discussionmentioning
confidence: 62%
“…Arbeit et al [13] have shown overall 13.6% incidence of DVT after groin dissection with no benefit of pharmacological heparin prophylaxis. Various studies have shown low incidence of DVT in Indian patients [14,15]. Apart from ethnicity, early ambulation and routine use of mechanical prophylaxis might have resulted in zero incidence of DVT/PE in the present series.…”
Section: Discussionmentioning
confidence: 62%
“…Patient-specific risk factors for VTE include age, gender, smoking history, race, BMI >25 kg/m 2 , prolonged immobility, higher performance status, past medical history, presence of varicose veins, serious lung disease or chronic respiratory insufficiency, pre-existing cardiac conditions, pregnancy, thrombophilia, previous history of PE, congestive heart failure, or trauma (14,18,(20)(21)(22)(23). Asian population may have a lower incidence of VTE which may be due to lower prevalence of factor V Leiden mutation and possibly lower levels of fibrinogen, factor VIIc and factor VIIIc (24). However, a recent study in China (22), found an overall incidence of VTE of 11.2% after lung surgery (without VTE prophylaxis which is not used routinely in China) and none of the patients had typical symptoms of VTE.…”
Section: Risk Factorsmentioning
confidence: 99%